Effects of anisotropy on dynamic void collapse and temperature rise in low-symmetry crystals. (September 2022) - Revil-Baudard, Benoit
Highlights: Role of plastic anisotropy of low-symmetry molecular energetic crystals on dynamic void collapse. FE simulations of voided tetragonal single-crystals subjected to dynamic plain strain loading reveal the effects of the crystal orientation with respect to the wave direction on void collapse. Maximum temperature rise and location of the temperature peaks depends on the crystal orientation. Abstract: An investigation into the role of plastic anisotropy on dynamic void collapse and temperature rise in low-symmetry crystals is presented. To describe the influence of local deformation and thermal history on the dynamic process, in this paper, we use the new anisotropic model for low-symmetry crystals developed in [1] . This constitutive model accounts for the influence of the symmetries of tetragonal lattice on both the elastic and plastic response. Based on the results of the finite-element (FE) simulations of voided PETN crystals subjected to dynamic plain strain loadings, it can be concluded that there are significant effects of the crystal orientation on void collapse and on the location of the temperature peaks, which are potential sites for ignition.